Types of ultraviolet filters and their combination used in sunscreen determine the appropriate sun protection factor values in vivo - Diah Puspitosari; Andini D. Anjani; Kartika Ruchiatan; Oki Suwarsa; Hartati P. Dharmadji; Eva K. Sutedja; Srie P. Gondokaryono; Trustia Rizqandaru; Reti Hindritiani (Journal of the Egyptian Women’s Dermatologic Society)
Background The application of sunscreen has been shown to prevent the detrimental effects of ultraviolet. The effectiveness of a sunscreen formulation protection against ultraviolet B is measured by sun protection factor (SPF) and its value determined by in vivo testing is still the gold standard. The consistency between the in vivo and in vitro SPF values is still interesting to investigate, including the influencing factors. Objective To analyze the correlation between the products’ manufacturer estimation in vitro SPF value with the in vivo SPF value and assessing determinant factors that may influence the in vivo SPF value. Patients and methods Ten sunscreen products from various manufacturers were tested in vivo using The European Cosmetic Toiletry and Perfumery Association (COLIPA) method. All the tested products in this study have the manufacturer’s estimated SPF value determined based on in vitro test conducted by the manufacturer. The Spearman correlation test was used for data analysis. Results All sunscreen products had the estimated SPF values of 30 and 50, for five products each. Nine products were in cream formulations and one in lotion formulation, as ‘day cream’ and ‘BB cream,’ respectively. Six sunscreen products had lower in vivo SPF values compared with the manufacturer’s SPF value estimation, whereas four products had shown higher values. Although statistical analysis showed P value of 0.63 that indicates no significant correlation between both of the SPF values. Several products with the appropriate and higher in vivo SPF values contain octocrylene as a photostabilizer and additional coating materials such as stearic acid, aluminum hydroxide, and alumina. Conclusion This study demonstrated that the appropriateness of the in vivo SPF value to in vitro-estimated SPF value may be influenced by the photostabilizer substance and combination with additional coating materials also can increase stability and efficacy of the products.